Analisis Keuntungan Produk Penjualan Sate Padang Menggunakan Metode Simplex - Ananda, Muhammad Rizki; Wijaya, Alief Achmad; Ritonga, Akbar Pramuja; Ritonga, Irmayanti (Universitas Labuhanbatu, 2024)
This study aims to analyze the products and queues at the sale of satay padang using Simplex Method with QM for Windows application.Sate padang sellers, as food sellers, face challenges in planning and managing satay portion inventory to achieve maximum product.This study applies the Simplex Method, a mathematical programming technique, to identify the optimal combination of product inventory that can improve product and customer queues.The research steps include analysis of historical sales data, identification of decision variables, as well as the formulation of mathematical models based on optimal goals.The QM for Windows application is used as a tool to run probability and random variable distribution methods and analyze the results. The study also evaluated the impact of optimization on products, queues, inventory efficiency, and customer satisfaction.The results of this study are expected to provide practical guidance to owners of sate padang or similar businesses in managing product inventory and planning sales.In addition, this study can be a contribution to the development of optimization methods that can be applied in the context of small and medium businesses, especially in the culinary sector.